Engaging in Rather than Disengaging from Stress: Effective Coping and Perceived Control - Dijkstra, Maria T. M.; Homan, Astrid C. (Frontiers in Psychology, 2016)
Being able to cope effectively with stress can help people to avoid negative consequences for their psychological well-being. The purpose of this study was to find out why some coping strategies are effective in reducing the negative effect of stressors on well-being and some are not. We argue that the degree to which such coping strategies engage or disengage people from stressful incidents is related to their perceived control of the situation that, in turn, is positively associated with their psychological well-being. We thus propose that the relationship between coping and psychological well-being is mediated by the extent of perceived sense of control. We collected cross-sectional data from a large heterogeneous sample (N = 543) in the Netherlands. We assessed seven different coping strategies, perceived control, and psychological well-being. Our results indeed revealed that strategies reflecting more engaged coping such as active confronting and reassuring thoughts, were associated with more sense of control and therefore to psychological well-being. In contrast, strategies reflecting disengagement coping, such as passive reaction pattern, palliative reaction, and avoidance, were associated with less perceived control, which in turn was negatively associated with psychological well-being. Results regarding the coping strategies expressing emotions and seeking social support were less straightforward, with the former being negatively associated with perceived control and psychological well-being, even though this strategy has stress engaging elements, and the latter only showing a positive indirect effect on psychological well-being via perceived control, but no positive main effect on well-being. These findings are discussed from the perspective of stress being an environment-perception-response process.